2018
DOI: 10.1021/acs.energyfuels.8b00949
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Phase Separation as a Hypothesis to Account for Nuclei or Nanoaggregate Formation by Asphaltenes in Toluene

Abstract: Here, the concept of suppression of phase separation is proposed to account for the solubility behavior of asphaltenes at high dilution in toluene under ambient conditions. Nuclei formation at concentrations near 90 mg L–1 is the consequence of reaching A1 fraction solubility, and phase separation is suppressed by the intercalation of sufficient A2 in these nuclei or nanoaggregates. Presumably, such intercalation leads to media penetration of the nuclei periphery, hindering the growth and allowing for nuclei d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 51 publications
5
52
0
Order By: Relevance
“…In this way and from a qualitative point of view, it can be expected that a material represented by the M2 model should have greater solubility than the M1 model. Consistent with these ideas, it should be noted that the A1-based aggregates form at very low concentrations and the addition of A2 on these aggregates prevents their growth beyond the colloidal size, i.e., keeps the A1 molecules dispersed [70]. In this sense, Figure 2 shows a model of molecular mechanisms that simulate the nanoaggregates between four asphaltene A1 molecules represented under the M1 model and three A2 represented under the M2 model.…”
Section: Physical-chemical Properties Of Heavy (Ho) Extra-heavy Crudmentioning
confidence: 56%
See 4 more Smart Citations
“…In this way and from a qualitative point of view, it can be expected that a material represented by the M2 model should have greater solubility than the M1 model. Consistent with these ideas, it should be noted that the A1-based aggregates form at very low concentrations and the addition of A2 on these aggregates prevents their growth beyond the colloidal size, i.e., keeps the A1 molecules dispersed [70]. In this sense, Figure 2 shows a model of molecular mechanisms that simulate the nanoaggregates between four asphaltene A1 molecules represented under the M1 model and three A2 represented under the M2 model.…”
Section: Physical-chemical Properties Of Heavy (Ho) Extra-heavy Crudmentioning
confidence: 56%
“…In this way and from a qualitative point of view, it can be expected that a material represented by the M 2 model should have greater solubility than the M 1 model. Consistent with these ideas, it should be noted that the A 1 -based aggregates form at very low concentrations and the addition of A 2 on these aggregates prevents their growth beyond the colloidal size, i.e., keeps the A 1 molecules dispersed [70]. In this sense, Figure 2 shows a model of molecular mechanisms that simulate the nanoaggregates between four asphaltene A 1 molecules represented under the M 1 model and three A 2 represented under the M 2 However, the stability of asphaltenes depends to a large extent on the content of resins present in the crude oil matrix, because they can avoid asphaltene-asphaltene interactions by positioning on the surface of the asphaltene aggregate, penetrating its microporous structure and finally breaking the aggregation system [72][73][74] Previous studies have reported that higher adsorption of the resins on the colloidal fractions showing a higher affinity for A1 than for A2, indicating that the resin-A1 interactions are more favorable than the A1-A1 interactions [70].…”
Section: Physical-chemical Properties Of Heavy (Ho) Extra-heavy Crudmentioning
confidence: 64%
See 3 more Smart Citations